Effects of exposure to volatile organic compounds on some clinical factors of exposed people: case study (Kermanshah national oil products distribution company) - Maryam Delfani; Maryam Mohammadi Rouzbahani; Nasrin Choobkar; Noushin Salimi (سلامت و محیط, 2022)
Background and Objective: Today, oil and gas industries are important resources for obtaining energy and income. During the production of oil and gas, very complex compounds that include organic and inorganic substances, petroleum hydrocarbons and aromatic and aliphatic compounds are transferred to the environment. benzene, toluene, ethylbenzene and xylenes, which are called BTEX for short, are very important monoaromatic pollutants. Therefore, the present study was conducted to investigate the effect of exposure to BTEX on some clinical factors of the exposed people in the oil warehouse and office workers in Kermanshah National Oil Products Distribution Company. Materials and Methods: This cross-sectional study was conducted in 2018. The samples of this study include the personnel working in the oil warehouse and the office staff of the National Oil Products Distribution Company in Kermanshah. After completing the demographic information of the participants in terms of the inclusion criteria and after collecting the results of the physiological tests of the employees, SPSS19 software was used for statistical analysis. Results: The results of the present study showed that the spirometric indices decreased in the workers exposed to BTEX compounds, but it was not statistically significant. Also, the number of red blood cells (6.73%) was significantly lower in non-administrative employees, as well as red white blood cells (6.61%), SGOT (10.14%) and SGPT (5.09%) in non-administrative employees. It has been more. Conclusion: The number of platelets was higher in office workers. Considering the dangers of BTEX pollution for human health, it is recommended to use preventive measures such as using a special mask and a shift work system.